Extraction, Partial Purification and Characterization of Lipase Enzyme from Different Animal and Plant Sources - Ahmed Salh Mahdy ALazawee; Ziad Tariq Sedrah (مجلة ديالى للعلوم الزراعية)
The study aimed to extract the lipase enzyme from different sources, estimate its enzymatic activity, choose the best sources in terms of enzymatic activity, partially purify, and characterize it. The enzyme was extracted from plant sources (pumpkin seeds, melon seeds, and orange peels). The enzyme extract was precipitated with ammonium sulfate at a saturation level of 80%. The dialysis and lyophilization processes were performed for the partially purified enzyme. The optimum temperature for the partially purified enzyme was 40°C and the optimum pH was 7. The enzyme activity of the plant sources was 2.598, 0.723, and 1.333 units g-1, respectively. Animal sources (chicken pancreas and intestinal tract of carp fish). The enzymatic activity of the animal sources was 4.122 and 6.532 units g-1, respectively. The highest activity was in the intestinal tract of carp fish. The protein concentration was 4.212 mg mL-1, the total activity was 1658.88 units, the number of purification times was 1.638 times, and the enzyme yield was 80.18% using tributyrin as a substrate. It can also be noted that the enzyme produced from the intestinal tract of common carp, which was rich in it, can be used in various industrial fields.